Testing of a palatable bait and compatible vaccine carrier for the oral vaccination of European badgers (Meles meles) against tuberculosis. Issue 6 (7th February 2017) - Gowtage, Sonya; Williams, Gareth A.; Henderson, Ray; Aylett, Paul; MacMorran, Duncan; Palmer, Si; Robertson, Andy; Lesellier, Sandrine; Carter, Stephen P.; Chambers, Mark A.
Highlights: First report of a physically stable bait for the delivery of BCG to wild badgers. BCG is stable within bait during storage and under simulated deployment conditions. Bait used to deliver oral biomarker to badgers to simulate oral delivery of vaccine. A highly palatable bait combined with a BCG-compatible vaccine carrier. Discussion of requirements for the components of a successful oral wildlife vaccine. Abstract: The oral vaccination of wild badgers ( Meles meles ) with live Bacillus Calmette–Guérin (BCG) is one of the tools being considered for the control of bovine tuberculosis (caused by Mycobacterium bovis ) in the UK. The design of a product for oral vaccination requires that numerous, and often competing, conditions are met. These include the need for a highly palatable, but physically stable bait that will meet regulatory requirements, and one which is also compatible with the vaccine formulation; in this case live BCG. In collaboration with two commercial bait companies we have developed a highly attractive and palatable bait recipe designed specifically for European badgers ( Meles meles ) that meets these requirements. The palatability of different batches of bait was evaluated against a standardised palatable control bait using captive badgers. The physical properties of the bait are described e.g. firmness and colour. The microbial load in the bait was assessed against European and US Pharmacopoeias. The bait was combined with an edible vaccine carrier made of hydrogenated peanut oil in which BCG vaccine was stable during bait manufacture and cold storage, demonstrating <0.5 log10 reduction in titre after 117 weeks' storage at −20 °C. BCG stability in bait was also evaluated at +4 °C and under simulated environmental conditions (20 °C, 98% Relative Humidity; RH). Finally, iophenoxic acid biomarkers were utilised as a surrogate for the BCG vaccine, to test variants of the vaccine-bait design for their ability to deliver biomarker to the gastrointestinal tract of individual animals. These data provide the first detailed description of a bait-vaccine delivery system developed specifically for the oral vaccination of badgers against Mycobacterium bovis using live BCG.